Learning climate and quality of Italian training courses in gynecology and obstetrics. (October 2019) - ,; Candiani, Massimo; Casarin, Jvan; Ciavattini, Andrea; Paola, Rossana Di; Greco, Pantaleo; Guaschino, Secondo; Marchesoni, Diego; Milani, Rodolfo; Rizzo, Nicola; Venturini, Pier Luigi; Valente, Elena; et al.
Abstract: Objectives: To evaluate the learning climate (LC) and quality of training in postgraduate training courses in gynecology and obstetrics in Italy, as essential element to improve the training quality of future medical specialists. Study Design: Web-based anonymous survey sent to all Italian trainees in gynecology and obstetrics to assess LC and quality of postgraduate training courses. This included sociodemographic information, details regarding training positions, and a 50-item validated Dutch Residency Educational Climate Test (D-RECT) questionnaire with 11 subscales (1–5 Likert scale). At the same time, the 24-items Fifth Year Training Questionnaire (FYT-Q) was submitted to all trainees at the fifth year of training to assess quality of life (burnout and depression), quality of training and final achieved competency level. Descriptive statistics were used to describe the main characteristics of the study population and for the D-RECT and the FYT-Q results. Results: One hundred seventy-eight trainees' responses were included from 13 departments, yielding a department response rate of 33%. The mean composite score of the D-RECT was 3.185 (SD 0.305). The subscales "Formal education" and "Role of specialty tutor" scored a mean of 2.751 (SD 0.123) and 2.757 (SD 0.130), respectively. Sixty-four FYT-Q evaluations were completed. The 33% of trainees reported more than 56 weekly working hours. At least one burnout episode during the training was reported by 61% of the trainees, and the 45% of them reported one or more episode of depression. More than 50% of trainees reported adequate autonomy for gynecologic ultrasound, obstetrics first level ultrasound, hysteroscopy, and cesarean section. In FYT-Q adequacy of training, teaching, surgical teaching, and tutoring values resulted equal to or less than 3 in a 1–5 Likert scale. Conclusions: D-RECT and FYT-Q questionnaires show a training that requires improvement, although the results do not seem to be completely consistent. D-RECT emphasizes the need for a better formal teaching and specialty tutors to ensure training with better LC. Interventions are needed to improve LC and quality of training in postgraduate training courses in gynecology and obstetrics in Italy.